Overexpression of PDE4D in mouse liver is sufficient to trigger NAFLD and hypertension in a CD36-TGF-β1 pathway: therapeutic role of roflumilast. (January 2022) - Tao, Xiang; He, Haiqing; Peng, Jiangtong; Xu, Rui; Fu, Jing; Hu, Yuting; Li, Li; Yang, Xiaoyan; Feng, Xiuling; Zhang, Chao; Zhang, Lingmin; Yu, Xiyong; et al.
Abstract: Emerging evidence has shown that nonalcoholic fatty liver disease (NAFLD) may be both a consequence and a cause of hypertension. Recent studies have demonstrated that phosphodiesterase 4 (PDE4)-cAMP signaling represents a pathway relevant to the pathophysiology of metabolic disorders. This study aims to investigate the impact and the underlying mechanism of PDE4 in the pathogenesis of NAFLD and its associated hypertension. Here we demonstrated that high-fat-diet (HFD) fed mice developed NAFLD and hypertension, with an associated increase in hepatic PDE4D expression, which can be prevented and even reversed by PDE4 inhibitor roflumilast. Furthermore, we demonstrated that hepatic overexpression of PDE4D drove significant hepatic steatosis and elevation of blood pressure. Mechanistically, PDE4D activated fatty acid translocase CD36 signaling which facilitates hepatic lipid deposition, resulting in TGF-β1 production by hepatocytes and excessive TGF-β1 signaling in vessels and consequent hypertension. Specific silencing of TGF-β1 in hepatocytes by siRNA using poly (β-amino ester) nanoparticles significantly normalized hepatic PDE4D overexpression-activated TGF-β1 signaling in vessels and hypertension. Together, the conclusions indicated that PDE4D plays an important role in the pathogenesis of NAFLD and associated hypertension via activation of CD36-TGF-β1 signaling in the liver. PDE4 inhibitor such as roflumilast, which is clinically approved for chronic obstructive pulmonary disease (COPD) treatment, has the potential to be used as a preventive or therapeutic drug against NAFLD and associated hypertension in the future. Graphical Abstract: PDE4 inhibitor Roflumilast, a prescription medicine used in chronic obstructive pulmonary disease treatment, reverses fatty liver and associated hypertension through inhibiting hepatic PDE4D-CD36-TGF-β1 hyperactivation-enhanced TGF-β1 signaling in vessels. ga1